Red cell sodium in DOCA-salt hypertension: a Brattleboro study - Talib, H K; Zicha, J (Life sciences, 1992)
The alteration of red cell Na+ content (Na+i), its causes and the possible relationship to the development of DOCA-salt hypertension were studied in Brattleboro rats. A pronounced hypertension developed in heterozygous (non-DI) animals that synthesize vasopressin (VP) although no substantial Na+i elevation was observed in their erythrocytes. In contrast, Na+i rose progressively in red cells of homozygous VP-deficient (DI) rats in which only marginal increase of systolic blood pressure was found after six weeks of DOCA-salt regimen. DOCA-salt treatment of non-DI rats did not cause major alterations in ouabain-resistant (OR) net Na+ uptake or ouabain-sensitive (OS) net Na+ extrusion but moderately increased furosemide-sensitive (FS) Rb+ uptake. The same treatment of DI rats doubled Na+i by an increased OR net Na+ uptake (due to a major elevation in both Na(+)-K+ cotransport and Na+ leak). Consequently, OS net Na+ extrusion was augmented in red cells of these animals. This was accompanied by an about threefold elevated FS Rb+ uptake. It can be concluded that a) the alterations of OR and/or OS Na+ or K+ transport observed in erythrocytes of Brattleboro DI rats are not essential for the development of severe DOCA-salt hypertension, b) red cell ion transport abnormalities revealed in DOCA-salt treated DI rats might be rather ascribed to cell potassium depletion, and c) increased inward Na(+)-K+ cotransport and Na+ leak causes red cell Na+i elevation that stimulates Na(+)-K+ pump activity.
Keywords: Blood Pressure; Hypertension; sodík; Bumetanide; zvířata; deoxykortikosteron; Sodium, Dietary; Hemoglobins; ženské pohlaví; techniky in vitro; Ouabain; Rats; nefrektomie; Erythrocytes; Biological Transport, Active; Female; Desoxycorticosterone; Rats, Brattleboro; Hematocrit; hypertenze; furosemid; erytrocyty; krysa rodu Rattus; ouabain; Nephrectomy; sodík dietní; Kinetics; kinetika; aktivní transport; Animals; Furosemide; Sodium; In Vitro Techniques; hemoglobiny; hematokrit; Rubidium; bumetanid; krevní tlak; rubidium; potkani Brattleboro